Designing Mobile Application Interaction for School Internal Communication using User-centered Design - Alivia Dewi Parahita; Dessi Puji Lestari; Ginar Santika Niwanputri (Universitas Multimedia Nusantara, 2020)
In order to fastened up the process, the school internal communication system has been changed from its conventional way using linking book and announcement letter, to messaging groups or mobile applications. This was done to create a good communication between teachers and parents for their children. But parent capability on using mobile application has been causing problems. In this paper, we present the result of our observation for the current school internal communication system problem and made the better solution. To make sure the application design matches with parent’s capability, the user-centered design method is applied. The final result of this study is a high-fidelity prototype of the application for parent side built using Sketch tools. The usability testing has been done to student parents. Based on the test result, this prototype has a good interaction, has a user-friendly interface for parents, and also already fulfill the usability goal and the user experience.